在类克尔介质腔中三能级原子的原子偶极矩的高阶压缩 - 卢俊; 许毅; 董传华 (上海大学学报(英文版), 2003)
O4; In this paper, evolution of the higher-order squeezing for atomic dipole of three-level atom in the Kerr-like medium is investigated. The atom discussed has two configurations and is driven by the single-mode coherent state field. Our results show that the squeezing effects are clearly influenced by nonlinear parameters, the initial atom state and the detuning.